Analysis of Factors Affecting Intention to Use and User Satisfaction of Paylater Using DeLone & McLean Adoption Model - Utari, Ulil Azmi; Fauziah, Yuli (Jurusan Informatika, 2023)
Purpose: This study aims to determine the factors that affect the intention to use and satisfaction of GoPayLater users in Yogyakarta, by assessing the relationship between variables so that recommendation for improvent can be given.Design/methodology/approach: This study uses the DeLone & McLean adoption model by Seddon which includes 5 constructs namely system quality, information quality, perceived usefulness, intention to use and user satisfaction. Primary data collection was conducted by distributing questionnaires using likert scale measurement to 128 GoPayLater users. The data analysis technique used is SEM-PLS to test the measurement model, structural model and test the hypothesis via SmartPLS software.Findings/results:Based on the results of hypothesis testing in this study, two hypotheses were rejected from eight hypothesises. These findings indicate that perceived usefulness has a positive and significant effect on intention to use, while the variables of system quality and information quality do not have a significant effect directly on intention to use GoPayLater. The R-Square test results show that system quality, information quality and perceived usefulness simultaneously have an effect of 34,4% on intention to use GoPayLater. This study also proves that variables of system quality, information quality and perceived usefulness have a positive and significant effect on GoPayLater user satisfacion, with the level of influence given simultaneously is 51,7% .Originality/value/state of the art: Several previous studies have tested GoPayLater from various aspects, but no research has been found that assesses the relationship and effect of system quality, information quality and perceived usefulness on intention to use and user satisfaction using the DeLone & McLean adoption model by Seddon.